Analyzing the influence of physical exercise interventions on social skills in children with autism spectrum disorder: insights from meta-analysis - Koh, Sung Hee (Frontiers in Psychology, 2024)
Introduction Children diagnosed with autism spectrum disorder (ASD) commonly encounter difficulties in social interactions and communication, significantly affecting their overall wellbeing. One proposed strategy to address these challenges is through physical exercise interventions. This study aims to conduct a meta-analysis to assess the impact of physical exercise interventions on the social skills of children with ASD. Methods To perform this meta-analysis, we followed the Preferred Reporting Items of Systematic Reviews and Meta-Analyses (PRISMA) Statement and the practical guide for transparent reporting of systematic reviews. Eligible studies included randomized controlled trials or quasi-experimental studies investigating the effects of physical exercise interventions on social skills among children with ASD. We used the standardized mean difference (SMD) to measure effect size. Results Sixteen studies were included in the meta-analysis. The results indicated a significant improvement in social skills among children with ASD following physical exercise interventions (SMD = −0.54, 95% CI = [−0.63; −0.44]). The moderator analysis underscored the crucial role of age in explaining the intervention outcomes for enhancing social skills, with interventions lasting more than 12 weeks recommended for better social skills improvement. Discussion The findings of this meta-analysis provide robust evidence supporting the efficacy of physical exercise interventions in enhancing the social skills of children with ASD. The moderator analysis underscores the importance of considering both the mean age and duration of interventions when implementing such programs. These results underscore the significance of physical exercise as a viable option for improving social skills in this population.